(Un-)Sichtbarkeiten Beiträge zum XXXI. Forum Junge Romanistik in Rostock (5.-7. März 2015) - Kern, Beate; Roger, Jennifer; Serafin, Stefan; Thode, Anna Charlotte (Forum Junge Romanistik, 2017)
The contributions to this volume deal with the concept of (in)visibility from the perspectives of linguistics, literary studies and cultural studies in the field of Romania and shed light on historical, social, linguistic and literary aspects. (In)visibility is to be understood as a gradual and potentially dynamic phenomenon that can be subject to developments and external influences and thus opens up a broad spectrum for different approaches and analyses. The volume thus contributes to structuring the field of research, establishing references to current discussions and at the same time demonstrating the diversity of the concept of (in)visibility. Thematically, the scope ranges from considerations of the visual dimension of space, (in)visibility of processes and developments, literary-medial procedures of (in)visualisation and censorship to the (in)visibility of social groups and linguistic actors as well as of individual identities and collective discourses.